The world of the prairie dog. - Costello, David F. (David Francis), 1904-1990. (Philadelphia, Lippincott, 1970)
Discusses the characteristics and behavior of prairie dogs, the ways in which the changing seasons affect their lives, their role in the ecological balance of their environment, and their relationship to man.
Bibliography: p. 147-153.
Keywords: Prairie dogs